Digital Teaching Style on Instagram Reels: Jerome Polin and Teacher Appreciation in Indonesia - Adelika, Lilis; Firda Harlidayana; Zara Mahfuza; Nur Zakia Khoironi; Vika Sihombing; Meisuri (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study addresses the problem of low teacher appreciation in Indonesia. The data are drawn from one of Jerome Polin’s Instagram Reels that compares teacher salaries with the price of an iPhone. Using a qualitative case study with sociolinguistic theories of style-shifting and multimodal discourse analysis, the study finds that Jerome combines humor, casual language, gestures, visual design, and captions to construct a teacher persona in digital space. These strategies make social critique both accessible and entertaining while reconstructing teacher identity performatively on social media. The study contributes theoretically to sociolinguistic discussions of style in multimodal digital contexts and provides practical recommendations for educators, content creators, and policymakers in developing effective communication strategies.